Cultural Differences in Fear of Negative Evaluation After Social Norm Transgressions and the Impact on Mental Health - Vaswani, Mamta; Esses, Victoria M.; Newby-Clark, Ian R.; Giguère, Benjamin (Frontiers in Psychology, 2022)
Social norm transgressions are assumed to be at the root of numerous substantial negative outcomes for transgressors. There is a prevailing notion among lay people and scholars that transgressing social norms can negatively impact one’s mental health. The present research aimed to examine this assumption, focusing on clinically relevant outcomes such as anxiety and depression. The present research further aimed to examine a social cognitive process for these outcomes in the form of fear of negative evaluations as a result of one’s norm transgressing behavior. Specifically, it examined whether it is negative evaluations about ourselves or about those close to us that mediates the effect of social norm transgressions, and whether those may vary as a function of culture. Results of the present research, including a study with a community sample (N = 410), suggest a positive association between social norm transgressions and psychological distress. Results also suggest that increased fear of negative evaluation mediates that association but does so differently for people from more collectivistic cultures and people from less collectivistic cultures. For people from more collectivistic cultures increased fear of negative evaluation of close others may mediate the association between social norm transgressions and psychological distress. However, for people from less collectivistic cultures that association may be mediated by increased fear of negative evaluation of oneself. Implications for research on consequences of social norm transgressions and cross-cultural differences in perceptions of such consequences are discussed as are practical implications for motivating social norm adherence and the maintenance of constructive social norms.